Comparing Feedback Types in Multimedia Learning of Speech by Young Children With Common Speech Sound Disorders: Research Protocol for a Pretest Posttest Independent Measures Control Trial - Doubé, Wendy; Carding, Paul; Flanagan, Kieran; Kaufman, Jordy; Armitage, Hannah (Frontiers in Psychology, 2018)
Children with speech sound disorders benefit from feedback about the accuracy of sounds they make. Home practice can reinforce feedback received from speech pathologists. Games in mobile device applications could encourage home practice, but those currently available are of limited value because they are unlikely to elaborate ‘Correct’/’Incorrect’ feedback with information that can assist in improving the accuracy of the sound. This protocol proposes a ‘Wizard of Oz’ experiment that aims to provide evidence for the provision of effective multimedia feedback for speech sound development. Children with two common speech sound disorders will play a game on a mobile device and make speech sounds when prompted by the game. A human ‘Wizard’ will provide feedback on the accuracy of the sound but the children will perceive the feedback as coming from the game. Groups of 30 young children will be randomly allocated to one of five conditions: four types of feedback and a control which does not play the game. The results of this experiment will inform not only speech sound therapy, but also other types of language learning, both in general, and in multimedia applications. This experiment is a cost-effective precursor to the development of a mobile application that employs pedagogically and clinically sound processes for speech development in young children.